Development of Local Food-Based Food Products to Expand Marketing Network in Kenjeran Bulak Sub District Surabaya - Wardhani, Nuruni Ika Kusuma; Hendrati, Ignatia Martha; Sishadiyati (Nusantara Science and Technology Proceedings, 2020)
Local Food according to most people, mentioning that various local foods are considered to contain a fairly low nutritional value and not modern or not modern, that in fact, local food has many advantages compared to imported foods. Because this local resource is included in it local food that has a closeness that is related to food security. development of the product covers aspects of the processing process, distribution to consumption at the household level. The area of Kenjeran Bulak sub-district is a Group of Housewives named SAKKE Group, whose business is to make food and drink or commonly known as food. SAKKE group every day make processed products and fruit juice drink SAKKE Group in Kenjeran area is still less developed, among others: 1) Less Varied for food and beverage types so it is necessary to the diversification of products, 2) For packaging/presentation relatively still simple using plastic place less hygienic, 3) Marketing done by SAKKE group has not been so wide. In implementing the Program utilization of science and technology in our community using the method of mentoring and training on mothers of SAKKE Group. By mentoring and training Product Diversification, Good and Attractive Packaging, and Online Marketing. With training and mentoring in SAKKE group mothers, The quality and quantity of locally produced food-based food products have increased, Diversification of new products, namely Black Dawet based on Mujaer fish, Increased marketing activity and increased sales turnover, Questionable business management with orderly business bookkeeping and increased knowledge and entrepreneurial motivation, so that they can make changes (innovations) in carrying out their business to expand the market and increase revenue.